One foot in and one foot out: reflecting on international collaboration - Adefila, Arinola; Spolander, Gary; Maia, Eduardo (Argumentum, 2023)
International Research Collaboration has been steadily increasing as higher education has become more marketized. Though there are many obvious benefits for collaborating internationally, there are also several challenges that are often not critically discussed. Beyond the issues inherent in unequal partnerships between rich and low-income countries, these kinds of partnerships can be problematic if they do not accentuate collaboration that permits enhanced opportunities to improve and challenge our ideas and share various experiences and knowledges. This paper presents a reflection of lived experiences by three academics who have been involved in International Research Collaboration for over forty years.